Impact of preoperative education on ostomy patients quality of life - Ažukienė, Barbora; Šimčikas, Dainius (Slauga. Mokslas ir praktika, 2021)
Human well-being is directly related to his health. Preoperative training of patients and selection of the optimal stoma location are probably the most important factors influencing the postoperative quality of life of stoma patients.Study aim - to determine the impact of preoperative training on the quality of life of stoma patients.Study methods. The analysis of the scientific literature and quantitative research was used for the survey, which was carried out by a written questionnaire. The patients interviewed were both inpatient and patients arriving for outpatient consultation. The survey was conducted in June-November, 2020, with the oral consent of the respondents. 150 questionnaires were distributed, 144 questionnaires were returned, but 6 of them were incomplete. Return of questionnaires - 92 percent.Results. The study found that patients, with whom the optimal bowel stoma location was not discussed before surgery, were significantly more likely to have poor quality of life, it also turned out that as many as one-fifth of patients did not receive any information about the stoma and were not acquainted with the peculiarities of intestinal stoma care, and almost half of the respondents received this information after the stoma opera-tion.Conclusions. Preoperative patient training and collaboration are directly related to patients’ quality of life after bowel stoma formation surgery.
Keywords: stoma; colostomy; ileostomy; knowledge; training